A qualitative study into the perceived barriers of accessing healthcare among a vulnerable population involved with a community centre in Romania - Siân George; Katy Daniels; Evridiki Fioratou (BMC, 2018)
Abstract Background Minority vulnerable communities, such as the European Roma, often face numerous barriers to accessing healthcare services, resulting in negative health outcomes. Both these barriers and outcomes have been reported extensively in the literature. However, reports on barriers faced by European non-Roma native communities are limited. The "Health Care Access Barriers" (HCAB) model identifies pertinent financial, structural and cognitive barriers that can be measured and potentially modified. The present study thus aims to explore the barriers to accessing healthcare for a vulnerable population of mixed ethnicity from a charity community centre in Romania, as perceived by the centre's family users and staff members, and assess whether these reflect the barriers identified from the HCAB model. Methods Eleven community members whose children attend the centre and seven staff members working at the centre participated in face-to-face semi-structured interviews, exploring personal experiences and views on accessing healthcare. The interviews were transcribed and analysed using an initial deductive and secondary inductive approach to identify HCAB themes and other emerging themes and subthemes. Results Identified themes from both groups aligned with HCAB's themes of financial, structural and cognitive barriers and emergent subthemes important to the specific population were identified. Specifically, financial barriers related mostly to health insurance and bribery issues, structural barriers related mostly to service availability and accessibility, and cognitive barriers related mostly to healthcare professionals' attitudes and discrimination and the vulnerable population's lack of education and health literacy. A unique theme of psychological barriers emerged from both groups with associated subthemes of mistrust, hopelessness, fear and anxiety of this vulnerable population. Conclusion The current study highlights healthcare access barriers to a vulnerable non-Roma native population involved with a charity community centre in Romania. The "Healthcare Access Barriers for Vulnerable Populations" (HABVP) model is proposed as an adaption to the existing HCAB model to account for the unique perceived barriers to healthcare for this population. Recommendations for future resolution of these identified barriers are proposed.